A case of syncopal convulsions triggered by glossopharyngeal neuralgia - Tasci, Irem; Beydilli, Ibrahim; Demir, Caner Feyzi; Balgetir, Ferhat; Gonen, Murat; Bakir, Meryem (Kare Publ, 2021)
Syncopal convulsions and epileptic seizures are clinically hard to distinguish and differ in terms of treatment approaches. It is important to consider the cardiac arrhythmias that impair cerebral perfusion in the differential diagnosis of antiepileptic treatment-resistant convulsions. Here, we offer a 72-year-old male patient glossopharyngeal neuralgia (GN) after swallowing associated with recurrent episodes of syncopal convulsions. The patient was successfully treated with temporary pacemaker and carbamazepine. This phenomenon is noteworthy in terms of both asystole triggered by GN and syncopal convulsions which are rare in the differential diagnosis of epileptic seizures.
Glossofarengeal nevraljinin tetiklediği senkopal konvülziyon olgusu
Keywords: Asystole; glossopharyngeal neuralgia; syncopal convulsion